Self-stratification membrane-free aqueous zinc-iodine secondary battery and construction method thereof
By adopting self-layered electrolyte and integrated electrode structure in zinc-iodine batteries, the shortcomings of existing zinc-iodine batteries in stable cycle times and charge and discharge rates are solved, high stability and fast charge and discharge are achieved, and the cost and discharge are reduced. Manufacturing cost and process complexity while improving recyclable performance.
Patent Information
- Application Number
- CN202411482932.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-11
AI Technical Summary
The existing membrane-free biphasic zinc-iodine batteries have shortcomings in terms of stable cycle times and charge and discharge rates, and the materials are costly, complex processes and difficult to recover.
The self-layered, membrane-free water-based zinc-iodine secondary battery design is adopted. By using an electrolyte composed of organic phase and aqueous phase in the battery, and combining an integrated electrode structure, high stability and rapid charging and discharging are achieved.
The battery has a high stable cycle number (≥700 times) and fast charging and discharging rate (charge and discharging current can reach 9.4mA/cm2), while reducing material manufacturing costs and process complexity, and improving the battery's recyclability performance.
Smart Images

Figure CN119419384A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of novel electrochemical batteries and new energy batteries, and specifically relates to a self-stratified, membraneless aqueous zinc-iodine secondary battery suitable for large-scale energy storage systems and a construction method thereof. Background Art
[0002] With the rapid advancement of the construction of a low-carbon society, the importance of grid-level energy storage systems that enable efficient use of renewable energy has become increasingly prominent. Rechargeable lithium-ion batteries have become the first choice for grid-level energy storage systems due to their mature technology and high energy density. However, due to limited raw material supply, geopolitical risks and inherent flammability, the widespread integration of lithium-ion batteries into grid-level energy storage systems that require strong durability, high safety and low cost still faces huge challenges. Therefore, it is of great significance to develop new rechargeable battery technologies as a viable supplement or alternative to lithium-ion batteries. Among them, aqueous zinc-iodine secondary batteries are considered to be one of the strong competitors for the next generation of green grid-level energy storage systems due to their excellent safety, eco-friendliness, low manufacturing cost and high energy density.
[0003] However, the iodine positive electrode of the zinc-iodine battery is prone to produce water-soluble polyiodides during the cycle process, resulting in the battery facing problems such as short life and fast self-discharge. To solve this problem, a large number of iodine host materials, electrolyte formulations, diaphragm materials, etc. have been developed to inhibit the dissolution and diffusion of polyiodides. For example, the invention patent application of CN118263544A discloses a biomass carbon as a host material for a static zinc-iodine battery cathode; the invention patent application of CN117219886A discloses an electrolyte and battery for a zinc-iodine battery; the invention patent application of CN116826314A discloses a zinc-iodine battery diaphragm and its battery. However, the materials described in these schemes often face the problems of high manufacturing cost, complex process and difficulty in recycling, which is not conducive to the further expansion of zinc-iodine battery production preparation.
[0004] Patent CN117219886A discloses a membraneless two-phase zinc-iodine battery and its electrolyte that achieves ultra-high capacity. The self-stratified electrolyte is prepared with tetramethylammonium iodide or tetrabutylammonium iodide and an organic solvent as the organic phase, and zinc iodide and potassium salt as the aqueous phase. By setting the battery as a self-stratified structure, the problems of high preparation cost, complicated process and difficult recycling of traditional zinc-iodine batteries are alleviated to a certain extent, and a zinc-iodine battery with good cycle stability and high capacity is obtained. Although the battery has a high capacity and good cycle stability, its charge and discharge rate is slow (≤3mA / cm 2 ), resulting in fewer stable cycles. Summary of the invention
[0005] In view of the problems of the existing membraneless two-phase zinc-iodine battery with low stable cycle times and slow charge and discharge rate, the present invention aims to provide a self-stratified, membraneless aqueous zinc-iodine secondary battery and its construction method. Through a new design of the battery as a whole, the self-stratified electrolyte solves the problem of multi-iodide shuttle and combines the integrated electrode structure design to achieve high stability (cycle times ≥ 700 times) and fast charging rate (charge and discharge current can reach 9.4 mA / cm 2 ) of zinc-iodine battery.
[0006] To achieve the above-mentioned purpose, the present invention first provides a self-stratified electrolyte, which consists of an organic phase and an aqueous phase, wherein the organic phase includes tetrabutylammonium iodide, an ionic liquid, iodine and acetonitrile; and the aqueous phase includes zinc sulfate, magnesium sulfate and deionized water.
[0007] The introduction of sulfate can separate the aqueous phase and the organic phase, while the hydrophobic iodine salt introduced into the organic phase can avoid the crosstalk of iodine substances between the two phases through complexation. In addition, the introduction of ionic liquid can not only improve the ionic conductivity of the organic phase, but also reduce the volatility and flammability of the organic phase through the salt effect. As a result, the self-stratified system can achieve efficient and stable energy storage by relying on the reversible redox reaction between the iodine positive electrode in the organic phase and the zinc negative electrode in the aqueous phase.
[0008] In one embodiment of the present invention, the ionic liquid includes at least one of 1-butyl-3-methylimidazolium hexafluorophosphate, 1,3-bis(2,6-diisopropylphenyl)imidazolium chloride, 2-chloro-1,3-dimethylimidazolium hexafluorophosphate, 1-n-butyl-3-methylimidazolium hexafluorophosphate, N-allyl-2-alkylpyridinium chloride, and chlorobispiperidinium hexafluorophosphate.
[0009] In one embodiment of the present invention, the volume ratio of the organic phase to the aqueous phase is 1:3-6; preferably 1:4-5.
[0010] In one embodiment of the present invention, the mass volume ratio of the tetrabutylammonium iodide and the ionic liquid is (0.5-1.0) g:1 mL.
[0011] In one embodiment of the present invention, the volume ratio of the mixture of tetrabutylammonium iodide and acetonitrile to the ionic liquid is 7:3.
[0012] In one embodiment of the present invention, the molar ratio of iodine to tetrabutylammonium iodide is (0-1):1.
[0013] In one embodiment of the present invention, the molar ratio of zinc sulfate to magnesium sulfate is (2-6):1.
[0014] In one embodiment of the present invention, the mass concentration of zinc sulfate in the aqueous phase is 1-3M.
[0015] The present invention also provides a method for preparing a self-stratified electrolyte, the preparation method comprising the following steps:
[0016] a) dissolving tetrabutylammonium iodide in acetonitrile, then mixing it with an ionic liquid, and adding iodine thereto to obtain an organic phase electrolyte;
[0017] b) dissolving zinc sulfate and magnesium sulfate in deionized water to obtain an aqueous electrolyte;
[0018] c) Mixing the organic phase with the aqueous phase can obtain a self-stratifying electrolyte.
[0019] In one embodiment of the present invention, after tetrabutylammonium iodide is dissolved in acetonitrile, the concentration of tetrabutylammonium iodide is 1-1.5M.
[0020] In one embodiment of the present invention, the volume ratio of the tetrabutylammonium iodide acetonitrile solution to the ionic liquid is 7:3.
[0021] In one embodiment of the present invention, in step a), after iodine is added, the concentration of iodine in the organic phase electrolyte is 0-1M.
[0022] In one embodiment of the present invention, in step b), in the aqueous electrolyte, the concentration of zinc sulfate is 1-3M, and the concentration of magnesium sulfate is 0.5-1M.
[0023] In one embodiment of the present invention, in step c), the volume ratio of the organic phase to the aqueous phase is 1:3-6; preferably 1:4-5.
[0024] The invention also discloses an aqueous zinc-iodine secondary battery comprising the self-stratified electrolyte.
[0025] In one embodiment of the present invention, the battery comprises a positive electrode current collector, a positive electrode current wire, a negative electrode current collector, a negative electrode current wire, a battery casing and a self-stratified electrolyte; the self-stratified electrolyte is filled in the battery, the positive electrode current wire is connected to the positive electrode current collector, the negative electrode current wire is connected to the negative electrode current collector, the negative electrode current wire passes through the positive electrode current collector and is led out to the outside of the battery casing together with the positive electrode current wire, the negative electrode current wire is not in direct contact with the positive electrode current collector and the positive electrode current wire and remains in an insulated state, and the positive electrode current collector is not in direct contact with the negative electrode current collector and remains in an insulated state.
[0026] The positive electrode current collector and the positive electrode current wire can guide the positive electrode current input / output of the battery; the negative electrode current collector and the negative electrode current wire can guide the negative electrode current input / output of the battery; and the self-stratified electrolyte provides active materials and realizes the current transfer inside the battery.
[0027] In one embodiment of the present invention, the positive electrode current collector is graphite felt; the positive electrode current wire is corrosion-resistant titanium or stainless steel; the negative electrode current collector is zinc; the negative electrode current wire is copper wire; and the battery casing is a PET plastic casing.
[0028] The present invention also discloses a method for preparing the aqueous zinc-iodine secondary battery, the method comprising the following steps:
[0029] a) Punch a hole in the zinc and connect it to the end of the insulated copper wire;
[0030] b) inserting the graphite felt into the copper wire connected with zinc, and avoiding direct contact between zinc and graphite felt;
[0031] c) inserting the positive electrode wire from the interface between the copper wire and the graphite felt to the bottom of the graphite felt, and avoiding contact between the titanium wire and the zinc or copper wire, to complete the preparation of the integrated electrode;
[0032] d) adding the self-stratified electrolyte to a battery having an integral electrode;
[0033] e) After the liquid is added, the copper wire and the titanium wire are guided to the outside of the battery housing, and the battery is sealed, thereby completing the construction of a self-stratified, membrane-free aqueous zinc-iodine secondary battery.
[0034] Beneficial effects:
[0035] (1) The electrolyte of the battery of the present invention is composed of an organic phase and an aqueous phase, wherein the organic phase is prepared by dissolving tetrabutylammonium iodide, 1-butyl-3-methylimidazolium hexafluorophosphate and iodine in acetonitrile, and the aqueous phase is composed of zinc sulfate, magnesium sulfate and deionized water. The self-stratified electrolyte of the present invention can firmly bind iodine species to the organic layer through the extraction effect, while avoiding the use of expensive ion exchange membranes, it also overcomes the problems of low iodine loading, fast capacity decay, high self-discharge rate, etc. faced by zinc-iodine batteries.
[0036] (2) The present invention uses tetrabutylammonium iodide as the positive electrode electrolyte salt, acetonitrile as the organic solvent, and adds ionic liquid thereto to prepare the organic phase. The hydrophobic iodine salt introduced into the organic phase can avoid the crosstalk problem of iodine substances between the two phases through complexation, and the introduction of ionic liquid can not only improve the ionic conductivity of the organic phase, but also reduce the volatility and flammability of the organic phase through the salt effect. The aqueous phase uses zinc sulfate as the negative electrode active material, and the addition of magnesium sulfate helps to promote the formation of a self-stratified system. In addition, the self-stratified system can achieve efficient and stable energy storage by relying on the reversible redox reaction between the iodine positive electrode in the organic phase and the zinc negative electrode in the aqueous phase.
[0037] (3) The battery with tetrabutylammonium iodide, ionic liquid and acetonitrile as the organic phase has excellent cycle stability, and the charging current density of the battery can reach 2C, which is about 9.4mA / cm 2 Even if the battery is charged and discharged at a higher current density, the battery can still maintain good cycle stability. The battery is 1C (211mAh / g 碘 ) current density for charge and discharge cycles, the battery discharge capacity is 127.5 mAh g after 700 constant current charge and discharge cycles. -1 , the capacity retention rate can reach 84.7%. Even if the battery is charged and discharged at a current density of 2C, the capacity retention rate can still reach 82.0% after 600 constant current charge and discharge cycles.
[0038] (4) The addition of iodine can provide additional iodine to the system, increase the iodine content of the system, and thus improve the energy density of the battery system. Even in a high iodine concentration environment of 2.2M, the battery charge and discharge current density can reach 11.8mA / cm 2 , and at 5.9mA / cm 2 At a current density of , the battery capacity retention rate can reach 94.7% after 200 cycles.
[0039] (5) The electrode structure of the battery of the present invention adopts an integrated design, which is composed of zinc and graphite felt connected in a bottom-up order through copper wire and titanium. The integrated electrode structure combined with the self-stratified electrolyte can enable the zinc-iodine battery to complete the rapid assembly of Ah-level batteries within a few hours, greatly simplifying the battery preparation procedure and process.
[0040] (6) The zinc-iodine battery of the present invention has good recyclability. On the one hand, when recycling, the electrode structure of the system can be directly taken out and disassembled for recycling. The self-stratified electrolyte can also be quickly recycled through steps such as liquid separation and rotary evaporation concentration. On the other hand, the recycled electrolyte can still maintain good cycle stability after battery reorganization.
[0041] (7) The raw materials used in the technical solution of the present invention are widely available and inexpensive, which can meet the requirements of large-scale production and is expected to promote the development of new large-scale energy storage systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Schematic diagram of the structure of the self-stratified, membraneless aqueous zinc-iodine secondary battery prepared in Example 1 and Example 2.
[0043] Figure 2 This is a diagram showing the actual charging and discharging effects of the self-stratified, membraneless aqueous zinc-iodine secondary battery prepared in Example 1.
[0044] Figure 3 This is the cycle performance diagram of the zinc-iodine battery of Example 1 (current density is 1C).
[0045] Figure 4 This is the cycle performance diagram of the zinc-iodine battery of Example 1 (current density is 2C).
[0046] Figure 5 Schematic diagram of the flammability test of the self-stratified electrolyte in Example 1.
[0047] Figure 6 This is the rate performance diagram of the zinc-iodine battery of Example 2 (the current density changes from 0.1, 0.2, 0.4, 0.6, 0.8, 0.1, 0.2, and 0.4C in sequence).
[0048] Figure 7 This is the cycle performance diagram of the zinc-iodine battery of Example 2 (current density is 0.4C).
[0049] Figure 8 This is the cycle performance diagram of the zinc-iodine battery of Comparative Example 1 (current density is 1C).
[0050] Fig. 9 This is the charging curve of the zinc-iodine battery of Comparative Example 2.
[0051] Fig.10 The test results of the recyclability of the large-capacity zinc-iodine battery prepared according to the method of Example 2 (current density is 0.2C). DETAILED DESCRIPTION
[0052] The present invention will be further described below in conjunction with specific embodiments, and it should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.
[0053] Example 1
[0054] A method for preparing a self-stratified electrolyte comprises the following steps:
[0055] a) preparing a 1 M acetonitrile solution of tetrabutylammonium iodide, and then mixing the solution with 1-butyl-3-methylimidazolium hexafluorophosphate in a volume ratio of 7:3 to obtain an organic phase electrolyte;
[0056] b) dissolving zinc sulfate and magnesium sulfate in water to obtain an aqueous electrolyte, wherein the concentration of zinc sulfate in the aqueous electrolyte is 2 M and the concentration of magnesium sulfate is 0.5 M;
[0057] c) The organic phase electrolyte and the aqueous phase electrolyte are mixed in a volume ratio of 1:5 to obtain a self-stratified electrolyte.
[0058] A method for preparing a self-stratified, membrane-free aqueous zinc-iodine secondary battery comprises the following steps:
[0059] a) Punch a hole through the zinc sheet of 1.6 cm (diameter) x 0.1 mm (thickness) and connect it to the end of the insulated copper wire;
[0060] b) inserting a graphite felt of 2 cm (length) × 2 cm (width) × 0.8 cm (height) into the copper wire connected with zinc, and avoiding direct contact between zinc and graphite felt;
[0061] c) inserting the titanium wire from the interface between the copper wire and the graphite felt to the bottom of the graphite felt, and avoiding contact between the titanium wire and the zinc or copper wire, thereby completing the preparation of the integrated electrode;
[0062] d) adding the self-stratified electrolyte with a total volume of 6 mL into a battery with an integrated electrode;
[0063] e) After the liquid is added, the copper wire and the titanium wire are guided to the outside of the battery housing, and the battery is sealed to complete the preparation of the self-stratified, membrane-free aqueous zinc-iodine secondary battery (see attached Figure 1 shown).
[0064] The prepared aqueous zinc-iodine secondary battery was left to stand for 12 hours and then subjected to charge and discharge cycles between 0.6 and 1.6 V. The battery charge and discharge process showed high reversibility, and its polyiodide always remained in the organic phase and did not diffuse into the aqueous phase (such as the attached Figure 2 When the battery is charged at 1C (211mAh / g 碘 ) current density for charge and discharge cycles, the battery discharge capacity is 127.5 mAh g after 700 constant current charge and discharge cycles. -1 , the capacity retention rate is about 84.7% (as shown in the attached Figure 3 When the battery is charged and discharged at a current density of 2C, the capacity retention rate after 600 constant current charge and discharge cycles is about 82.0% (as shown in the attached figure). Figure 4 shown).
[0065] The self-stratifying electrolyte prepared in Example 1 was placed in an open watch glass and then ignited with an open flame to determine the flammability of the electrolyte.
[0066] As attached Figure 5 It is shown that the electrolyte has low flammability and excellent safety.
[0067] Example 2
[0068] A method for preparing a self-stratified electrolyte comprises the following steps:
[0069] a) preparing a 1 M acetonitrile solution of tetrabutylammonium iodide, then mixing the solution with 1-butyl-3-methylimidazolium hexafluorophosphate in a volume ratio of 7:3, and adding iodine to the solution so that the overall iodine concentration reaches 2.2 M to obtain an organic phase electrolyte;
[0070] b) dissolving zinc sulfate and magnesium sulfate in water to obtain an aqueous electrolyte, wherein the concentration of zinc sulfate in the aqueous electrolyte is 2 M and the concentration of magnesium sulfate is 0.5 M;
[0071] c) The organic phase electrolyte and the aqueous phase electrolyte are mixed in a volume ratio of 1:5 to obtain a self-stratified electrolyte.
[0072] A method for preparing a self-stratified, membrane-free aqueous zinc-iodine secondary battery comprises the following steps:
[0073] a) Punch a hole through the zinc sheet of 1.6 cm (diameter) x 0.1 mm (thickness) and connect it to the end of the insulated copper wire;
[0074] b) inserting a graphite felt of 2 cm (length) × 2 cm (width) × 0.8 cm (height) into the copper wire connected with zinc, and avoiding direct contact between zinc and graphite felt;
[0075] c) inserting the titanium wire from the interface between the copper wire and the graphite felt to the bottom of the graphite felt, and avoiding contact between the titanium wire and the zinc or copper wire, thereby completing the preparation of the integrated electrode.
[0076] d) adding the self-stratified electrolyte with a total volume of 6 mL into a battery with an integrated electrode;
[0077] e) After the liquid is added, the copper wire and the titanium wire are guided to the outside of the battery housing, and the battery is sealed, thereby completing the preparation of the self-stratified, membrane-free aqueous zinc-iodine secondary battery.
[0078] The prepared aqueous zinc-iodine secondary battery was left to stand for 12 hours, and then cycled at different current densities of 0.1, 0.2, 0.4, 0.6, 0.8, 0.1, 0.2, and 0.4 C at 0.6-1.6 V. The battery capacity reached 40.1 mAh at 0.1 C, and reached 11.8 mA / cm 2 ) The current density capacity can reach 21.8mAh, and the capacity retention rate is 54.4% (as shown in the attached Figure 6 In addition, in the long cycle stability test, the battery was cycled 200 times at a current density of 0.4C (energy density ~110.3Wh kg -1 碘 ), the capacity retention rate is as high as 94.7%, and the coulombic efficiency is close to 100% (such as the attached Figure 7 shown).
[0079] Comparative Example 1
[0080] The difference between Comparative Example 1 and Example 1 is that the preparation method of the self-stratified electrolyte is different.
[0081] A method for preparing a self-stratified electrolyte is as follows:
[0082] a) mixing acetonitrile and 1-butyl-3-methylimidazolium hexafluorophosphate in a volume ratio of 7:3, and then adding iodine thereto so that the iodine concentration is 0.7 M to obtain an organic phase electrolyte;
[0083] b) dissolving zinc sulfate and magnesium sulfate in water to obtain an aqueous electrolyte, wherein the concentration of zinc sulfate in the aqueous electrolyte is 2 M and the concentration of magnesium sulfate is 0.5 M;
[0084] c) taking the organic phase electrolyte and the aqueous phase electrolyte, mixing them in a volume ratio of 1:5 to obtain a self-stratified electrolyte.
[0085] The prepared aqueous zinc-iodine secondary battery was left to stand for 12 hours and then cycled at a current density of 1C between 0.6 and 1.6 V. Figure 8 As shown, when there is no tetrabutylammonium iodide in the system, due to the low solubility of iodine in acetonitrile and its easy diffusion into the water layer, the battery iodine utilization rate is low, the specific capacity is less than 100mAh / g, and after 600 cycles, the battery begins to become unstable.
[0086] Comparative Example 2
[0087] The difference between Comparative Example 2 and Example 1 is that the preparation method of the self-stratified electrolyte is different.
[0088] A method for preparing a self-stratified electrolyte is as follows:
[0089] a) preparing a 0.7 M tetrabutylammonium iodide acetonitrile solution to obtain an organic phase electrolyte;
[0090] b) dissolving zinc sulfate and magnesium sulfate in water to obtain an aqueous electrolyte, wherein the concentration of zinc sulfate in the aqueous electrolyte is 2 M and the concentration of magnesium sulfate is 0.5 M;
[0091] c) taking the organic phase electrolyte and the aqueous phase electrolyte, mixing them in a volume ratio of 1:5 to obtain a self-stratified electrolyte.
[0092] As attached Fig. 9 As shown, when there is no 1-butyl-3-methylimidazolium hexafluorophosphate in the system, the battery cannot be charged normally due to the lack of ion balance and the change of charge between the two phases during the charging and discharging process, indicating that 1-butyl-3-methylimidazolium hexafluorophosphate is important for the stability of the system.
[0093] Recyclability test
[0094] 1. Battery recycling
[0095] After the self-stratified, membrane-free aqueous zinc-iodine secondary battery was left to stand for 12 hours, it was cycled at a current density of 0.2C between 0.6 and 1.6 V, and then the battery was disassembled. The electrolyte was separated using a separatory funnel to obtain a recovered aqueous phase and a recovered organic phase. The electrode was washed with acetonitrile three times, the washing liquid was combined with the recovered organic phase, and the excess acetonitrile was evaporated using a rotary evaporator to achieve the concentration of the organic phase.
[0096] Among them, the self-stratified, membrane-free aqueous zinc-iodine secondary battery is prepared according to the scheme of Example 2, except that the size of the battery is changed. The specific preparation method is as follows:
[0097] a) Punch a hole through the zinc sheet of 4.6 cm (diameter) x 0.1 mm (thickness) and connect it to the end of the insulated copper wire;
[0098] b) inserting a graphite felt of 5 cm (length) × 6.4 cm (width) × 0.8 cm (height) into the copper wire connected with zinc, and avoiding direct contact between zinc and graphite felt;
[0099] c) inserting the titanium wire from the interface between the copper wire and the graphite felt to the bottom of the graphite felt, and avoiding contact between the titanium wire and the zinc or copper wire, thereby completing the preparation of the integrated electrode.
[0100] d) adding a self-stratified electrolyte having a total volume of 48 mL into a battery having an integrated electrode, wherein the preparation method of the self-stratified electrolyte is the same as that of Example 2;
[0101] e) After the liquid is added, the copper wire and the titanium wire are guided to the outside of the battery housing, and the battery is sealed, thereby completing the preparation of the self-stratified, membrane-free aqueous zinc-iodine secondary battery.
[0102] 2. Preparation of recovered electrolyte
[0103] Add acetonitrile to the concentrated organic phase in step 1 to keep the volume of the organic phase consistent with the volume of the organic phase before recovery, and mix it with the recovered water phase obtained in step 1 to obtain a recovered electrolyte.
[0104] 3. Preparation of recycled batteries: The recycled batteries are prepared according to the preparation method of the self-stratified, membraneless aqueous zinc-iodine secondary battery in step 1.
[0105] The battery recyclability test results are shown in the attached Fig.10 As shown, there is almost no decline in battery capacity after the battery is recycled and reassembled compared to before recycling, indicating that the self-stratified, membrane-free aqueous zinc-iodine secondary battery has excellent renewability.
[0106] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A self-stratifying electrolyte, characterized in that: The electrolyte consists of an organic phase and an aqueous phase, wherein the organic phase consists of tetrabutylammonium iodide, an ionic liquid, iodine and acetonitrile, and the molar ratio of iodine to tetrabutylammonium iodide is (0-1):1; the aqueous phase consists of zinc sulfate, magnesium sulfate and deionized water, and the volume ratio of the organic phase to the aqueous phase is 1:3-6.
2. The self-stratifying electrolyte according to claim 1, characterized in that The mass volume ratio of the tetrabutylammonium iodide and the ionic liquid is (0.5-1.0) g:1 mL, and the volume ratio of the mixture of the tetrabutylammonium iodide and acetonitrile to the ionic liquid is 7:3; the ionic liquid includes at least one of 1-butyl-3-methylimidazolium hexafluorophosphate, 1,3-bis(2,6-diisopropylphenyl)imidazolium chloride, 2-chloro-1,3-dimethylimidazolium hexafluorophosphate, 1-n-butyl-3-methylimidazolium hexafluorophosphate, N-allyl-2-alkylpyridinium chloride, and chlorobipiperidinium hexafluorophosphate.
3. The self-stratifying electrolyte according to claim 1, characterized in that The molar ratio of zinc sulfate to magnesium sulfate is (2-6):1, and the mass concentration of zinc sulfate in the aqueous phase is 1-3M.
4. A method for preparing a self-stratified electrolyte according to any one of claims 1 to 3, characterized in that: The following steps are involved: a) dissolving tetrabutylammonium iodide in acetonitrile, then mixing it with an ionic liquid, and adding iodine thereto to obtain an organic phase electrolyte; b) dissolving zinc sulfate and magnesium sulfate in deionized water to obtain an aqueous electrolyte; c) Mixing the organic phase with the aqueous phase can obtain a self-stratifying electrolyte.
5. The preparation method according to claim 4, wherein in step a), after tetrabutylammonium iodide is dissolved in acetonitrile, the concentration of tetrabutylammonium iodide is 1-1.5M, and after iodine is added, the concentration of iodine in the organic phase electrolyte is 0-1M.
6. The preparation method according to claim 4, wherein in step b), in the aqueous electrolyte, the concentration of zinc sulfate is 1-3M, and the concentration of magnesium sulfate is 0.5-1M.
7. An aqueous zinc-iodine secondary battery comprising the self-layered electrolyte according to any one of claims 1 to 3.
8. The aqueous zinc-iodine secondary battery according to claim 7, characterized in that: The battery comprises a positive electrode current collector, a positive electrode current wire, a negative electrode current collector, a negative electrode current wire, a battery shell and a self-stratified electrolyte; the self-stratified electrolyte is filled in the battery, the positive electrode current wire is connected to the positive electrode current collector, the negative electrode current wire is connected to the negative electrode current collector, the negative electrode current wire passes through the positive electrode current collector and is led out to the outside of the battery shell together with the positive electrode current wire, the negative electrode current wire is not in direct contact with the positive electrode current collector and the positive electrode current wire and remains in an insulated state, and the positive electrode current collector is not in direct contact with the negative electrode current collector and remains in an insulated state.
9. The aqueous zinc-iodine secondary battery according to claim 8, characterized in that: The positive electrode current collector is graphite felt; the positive electrode current wire is corrosion-resistant titanium or stainless steel; the negative electrode current collector is zinc; the negative electrode current wire is copper wire; and the battery shell is a PET plastic shell.
10. A method for preparing an aqueous zinc-iodine secondary battery according to any one of claims 7 to 9, characterized in that: The following steps are involved: a) Punch a hole in the zinc and connect it to the end of the insulated copper wire; b) inserting the graphite felt into the copper wire connected with zinc, and avoiding direct contact between zinc and graphite felt; c) inserting the positive electrode wire from the interface between the copper wire and the graphite felt to the bottom of the graphite felt, and avoiding contact between the titanium wire and the zinc or copper wire, to complete the preparation of the integrated electrode; d) adding the self-stratified electrolyte to a battery having an integral electrode; e) After the liquid is added, the copper wire and the titanium wire are guided to the outside of the battery housing, and the battery is sealed, thereby completing the construction of a self-stratified, membrane-free aqueous zinc-iodine secondary battery.
Citation Information
Patent Citations
Zinc-iodine battery diaphragm and battery thereof
CN116826314A
Electrolyte of zinc-iodine battery and battery
CN117219886A
Biomass carbon used as host material for static zinc-iodine battery cathode
CN118263544A